Implementasi Bimbingan Belajar Pada Siswa Kesulitan Matematika Di SDN Badran Surakarta - Melati, Nurhidayah Prima; , Dr Achmad Fathoni, M.Pd (2017)
This study aims to describe: 1) Steps of learning guidance for students who have difficulty mathematic in SDN Badran Surakarta, 2) Obstacles experienced by learners mathematic in SDN Badran Surakarta, 3) Efforts made by teachers in overcoming difficulties mathematic in SDN Badran Surakarta. This type of research is qualitative research. Data collection techniques used were interviews, observation, and documentation. Data analysis techniques use interactive analysis. Techniques to check the validity of data using triangulation of sources and techniques. The results of the study indicate that: 1) learning guidance steps for students who have difficulty in mathematic: a) Identification of cases, (1) through learning outcomes, (2) how to solve problems given by teachers, b) Problem identification, difficulties mathematic, c) diagnosis, lack of interest in learning, d) prognosis of difficult mathematic can be overcome, e) problem solving group counseling suitable for learners, f) evaluation and follow up, learning guidance activities can improve learners learning outcomes. 2) the barriers to learning the mathematic: a) The lack of learning media, b) the weakness of counting learners, 3) the efforts of teachers: a) utilization of objects around, b) provide problems according to the ability of learners.